Pathology of the Head and Neck - Cardesa, Antonio; Slootweg, Pieter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Head and neck pathology is increasingly becoming an attractive field for the new generations of pathologists, fully aware that in the era of specialization the information contained in the treatise of general surgical pathology, although extremely valuable to create the basis of their knowledge, does not provide in its full picture the specific knowledge required to meet current diagnostic and prognostic requirements. The book Pathology of the Head and Neck presents in a single volume the most pertinent and updated information needed by the interested readers. Its contents have been divided into ten chapters. The first one covers the spectrum of precursor and neoplastic lesions of the squamous epithelium. It is followed by chapters devoted to nasal cavities and paranasal sinuses, oral cavity, maxillofacial skeleton and teeth, salivary glands, nasopharynx and Waldeyer`s ring, larynx and hypopharynx, ear and temporal bone, neck and neck dissection, as well as eye and ocular adnexa. The authors of the different chapters have been selected among internationally recognized experts, all of them members of the Working Group on Head and Neck Pathology of the European Society of Pathology.
Benign and Potentially Malignant Lesions of the Squamous Epithelium and Squamous Cell Carcinoma -- Nasal Cavity and Paranasal Sinuses -- Oral Cavity -- Maxillofacial Skeleton and Teeth -- Major and Minor Salivary Glands -- Nasopharynx and Waldeyer’s Ring -- Larynx and Hypopharynx -- Ear and Temporal Bone -- Cysts and Unknown Primary and Secondary Tumours of the Neck, and Neck Dissection -- Eye and Ocular Adnexa.
Keywords: Pathology; Otorhinolaryngology; Oral surgery; Maxillofacial surgery; Ophthalmology; Pathology; Otorhinolaryngology; Oral and Maxillofacial Surgery; Ophthalmology